The ontology of social fluency and the reformulation of theological dogmatic from metaphysics of becoming - Romero Moñivas, Jesús (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper has two fundamental objectives: firstly, to defend the necessity that the social theory enters inside the dialogue between the sciences and theology. For it is explicated the case of convergence that it can exists among science, philosophy, social theory and theology under the new flowing ontology or metaphysics of becoming. Secondly, after the presentation of ontology of social fluency and of metaphysics of becoming, it is defended a reformulation of the dogmatic theology from a more dynamic and more evolutionary paradigm characteristic of modern science and philosophy, a less static philosophy than the Greek paradigm that up to now has served as philosophical foundation to the theological constructions.
Keywords: metaphysics of becoming; dogmatic theology; ontology of social fluency; theology-science relationships